Toxicological Effects of Leather Dyes On Serum Cholesterol of Fresh Water Teleost, Cirrhinus Mrigala (Ham.) - S.AFAQ.; K.S.RANA; M.A.LONE (International Journal of Pharma and Bio Sciences, 2010)
The fresh water Teleost, Cirrhinus mrigala (Ham. were treated with two leather dyes as in tables 1,2 and Fig.A,B) The serum cholesterol shows decreasing trend on exposure to Bismarck brown and Acid leather brown at different time intervals and at all three concentrations. However, the effect was more in Acid leather brown exposure. After Bismarck brown and acid leather brown exposure, the cholesterol decreased. It may be due to utilization of cholesterol in exposed fish and hindrance in metabolism. The serum cholesterol showed a decrease with an increase in the exposure time is highly significant The cholesterol was estimated by the method of Zak et al. (1954).The cholesterol reacts with ferric ions in the acid solution of ferric chloride and sulphuric acid. This reaction involved the "3 hydroxy-5-ene" part of the cholesterol molecule, which is dehydrated to form cholesta-3, 5, diene and is then oxidized by the sulphuric acid to link two molecules as biocholestra-3, 5 diene. This obtained substance is finally sulphonated by sulphuric acid in the presence of metal ions (Fe+3) and the red colored disulphuric acid having a high molecular extinction coefficient is formed The fresh water fishes were treated with two leather dyes as in (tables 1&2) the serum cholesterol shows decreasing trend on exposure to Bismarck brown and Acid leather brown at different time intervals (24 hrs, 48 hrs, 96 hrs and 1 week) and at all three concentrations. However, the effect was more in Acid leather brown exposure. After Bismarck brown and Acid leather brown exposure, the cholesterol decreased. It may be due to utilization of cholesterol in exposed fish and hindrance in metabolism.